Environment in the lives of children and families Perspectives from India and the UK - Phoenix, Ann (Bristol University Press, 2017)
Available Open Access under CC-BY licence. How do environmental policies link to dynamic and relational family practices for children and parents? This Policy Press Short presents innovative cross-national research into how 'environment' is understood and negotiated within families, and how this plays out in everyday lives. Based on an ESRC study that involved creative, qualitative work with families in India and the UK who live in different contexts, this book illuminates how environmental practices are negotiated within families, and how they relate to values, identities and society. In doing so, it contributes to understanding of the ways in which families and childhood are constructed as sites for intervention in climate change debates. In an area that is increasingly of concern to governments, NGOs and the general public, this timely research is crucial for developing effective responses to climate change.